2006
DOI: 10.3758/bf03194007
|View full text |Cite
|
Sign up to set email alerts
|

Cross-alphabet and cross-modal long-term priming in Serbian and English

Abstract: In Experiments 1 and 2, we investigated long-term repetition priming effects in Serbian under crossalphabet and cross-modal conditions. In both experiments, results followed the same pattern: significant priming in all conditions and no significant reduction in priming in the cross-modal as opposed to the cross-alphabet condition. These results are different from those obtained in English (Experiment 3), in which a modality shift led to a reduction in priming. The findings are discussed within a theoretical fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The letter height task is sensitive to prior orthographic processing of the target word (produced by prior reading or visualization of the word), but it appears that this orthographic processing has to be of the target word itself and not of a word with a similar appearance. In keeping with the terminology of Bowers et al (2002;Havelka et al, 2006), the mediating representation for the letter height task appears to be lexicalorthographic.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The letter height task is sensitive to prior orthographic processing of the target word (produced by prior reading or visualization of the word), but it appears that this orthographic processing has to be of the target word itself and not of a word with a similar appearance. In keeping with the terminology of Bowers et al (2002;Havelka et al, 2006), the mediating representation for the letter height task appears to be lexicalorthographic.…”
Section: Resultsmentioning
confidence: 99%
“…Theories of visual word perception generally propose that phonological representations play an important role, with some theories arguing that phonology plays the dominant role (e.g., Ashby & Martin, 2008;Conrad, Grainger, & Jacobs, 2007;Frost, 1998;Lukatela, Eaton, Lee, Carello, & Truvey, 2002; for review, see Rastle & Brysbaert, 2006). Recent researchers using implicit memory for verbal materials have likewise argued that phonological representations play an important role in visual priming (e.g., Brooks et al, 1999;Havelka et al, 2006;Lukatela et al, 2007;Lukatela, Eaton, Sabadini, & Turvey, 2004;Peretz, Lussier, & Be ´land, 1998;Rueckl & Mathew, 1999;Ryan et al, 2001; see influence of spelling-sound inconsistencies, modality-specific encoding strategies induced by mixed-list designs) and found no difference between cross-modal and intramodal priming on perceptual identification, WSC, and WFC. T. Curran et al (1999) and Loveman et al (2002) also reported conditions under which crossmodal and intramodal priming were equal for visual priming tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Further evidence for the beneficial effect of an existing phonological representation is provided by research on long-term priming effects. Such effects are stronger when the study and test words are presented in the same modality (usually visual-visual) than when modality is changed (from verbal to visual) between study and test (e.g., Havelka, Bowers, & Jankovic, 2006). However, a change of modality does not eliminate the priming effect; rather, it only tends to reduce the effect (Havelka et al, 2006).…”
Section: Introductionmentioning
confidence: 87%
“…Such effects are stronger when the study and test words are presented in the same modality (usually visual-visual) than when modality is changed (from verbal to visual) between study and test (e.g., Havelka, Bowers, & Jankovic, 2006). However, a change of modality does not eliminate the priming effect; rather, it only tends to reduce the effect (Havelka et al, 2006). This suggests that the visual-visual long-term priming effects are due partly to the generation or activation of a phonological representation.…”
Section: Introductionmentioning
confidence: 96%
“…Five items giving rise to more than 30% of errors were excluded from the analyses (for similar approach, e.g., Havelka, Bowers, & Jankovic, 2006;Kouider & Dupoux, 2005). For each participant and for each context, both RTs longer than 1800 ms and those greater than 2.5 standard deviations above and below the participant's overall response were excluded from the analyses.…”
Section: Experiments 1a: Auditory Grammatical Priming With a Short Isimentioning
confidence: 99%